Pengaruh Kepemimpinan Terhadap Stress Kerja Pegawai Pada Kantor Kementerian Agama Kab. Maros - Ulfa Hidayati; Tenri Jaya (STIE AMKOP, 2023)
Human Resources can be considered as the most important part of a company or organization. The element of human resources is not only employees, but also leaders. Where leaders must pay a lot of attention to their employees. This is what happened to the office of the Ministry of Religion Kab. Maros, where within 3 years there has been a change of Head of Office every one year during 2022, causing employees to have to adapt to the various Leadership Styles of each Head of Office. This study aims to explain the effect of leadership through the variable Job Stress using descriptive quantitative research methods. The number of research samples is less than 100, so all members of the population are used as respondents, which is equal to 58 respondents. The size scale used is the Likert scale. Based on the results of the study, that the high or low of the leadership variable has an effect but not significant on employee work stress. The results of statistical tests have proven that there is no significant effect of the leadership variable on employee work stress. Keywords: Human resources, leadership, work stress